CONVERSION OF PROSODIC CHARACTERISTICS BASED ON THE PITCH CONTOUR PARAMETRIZATION - V. A. Zakharyeu; A. A. Petrovsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A method of prosodic characteristics conversion based on the pitch contour parameterization, beside Patterson special points and Gillet conversion model, is presented in this paper. The comparison analysis showed better quality of proposed method versus canonical method of pitch Gaussian normalization. Therefore, it has a greater future for use in the conversion systems from the standpoint of the criterion of recognition.